The Abnormality of Topological Asymmetry in Hemispheric Brain Anatomical Networks in Bipolar Disorder - Wang, Bin; Li, Ting; Zhou, Mengni; Zhao, Shuo; Niu, Yan; Wang, Xin; Yan, Ting; Cao, Rui; Xiang, Jie; Li, Dandan (Frontiers in Neuroscience, 2018)
Convergent evidences have demonstrated a variety of regional abnormalities of asymmetry in bipolar disorder (BD). However, little is known about the alterations in hemispheric topological asymmetries. In this study, we used diffusion tensor imaging to construct the hemispheric brain anatomical network of 49 patients with BD and 61 matched normal controls. Graph theory was then applied to quantify topological properties of the hemispheric networks. Although small-world properties were preserved in the hemispheric network of BD, the degrees of the asymmetry in global efficiency, characteristic path length and small-world property were significantly decreased. More changes in topological properties of the right hemisphere than those of left hemisphere were found in patients compared with normal controls. Consisted with such changes, the nodal efficiencies in patients with BD also showed less rightward asymmetry mainly in the frontal, occipital, parietal, and temporal lobes. In contrast to leftward asymmetry, significant rightward asymmetry was found in supplementary motor area of BD, and attributed to more deficits in nodal efficiencies of the left hemisphere. Finally, these asymmetry score of nodal efficiencies in the inferior parietal lobule and rolandic operculum were significantly associated with symptom severity of BD. Our results suggested that abnormal hemispheric asymmetries in brain anatomical networks were associated with aberrant neurodevelopment, and providing insights into the potential neural biomarkers of BD by measuring the topological asymmetry in hemispheric brain anatomical networks.